Effectiveness of Self-Management Techniques Based on Islamic Counselling in Reducing Social Media Addiction Among Students - Maya Chofifah Silalahi; Ira Suryani (MASI Mandiri Edukasi, 2025)
This study aims to examine the effectiveness of Islamic guidance services incorporating self-management techniques in reducing the level of social media addiction among students at Al-Ulum High School in Medan. The background of the research stems from the increasing addictive behaviour towards social media among adolescents, which negatively impacts academic, social, and spiritual aspects. An Islamic approach is applied because it emphasises self-awareness, behavioural control, and the implementation of moral and spiritual principles, such as muhasabah (self-reflection), istiqamah (consistency), and murāqabah (self-monitoring). The research method employs a quantitative approach, utilising a pre-experimental one–group pretest–posttest design. The research sample consists of 19 tenth-grade students selected purposively because they exhibited symptoms of social media addiction. Data were collected through a social media addiction questionnaire that had been tested for validity and reliability (Cronbach’s Alpha = 0.786). Data analysis was conducted using the Wilcoxon Signed Rank Test with a significance level of 0.05. The results showed a significant decrease in students' social media addiction levels, with the average score dropping from 77.9 (high category) to 57.6 (low to moderate category), and a significance value of 0.000 < 0.05. These findings demonstrate that Islamic counselling services using self-management techniques are effective in enhancing self-regulation and reducing addictive behaviour towards social media.